Social media use among adolescents with limited family support: Insights from Uses and Gratifications Theory - Dessy Trisilowaty; Yuyun Wahyu Izzati Surya; Titik Puji Rahayu (C-DISC, 2026)
This study examines social media use among adolescents from broken-home family backgrounds, focusing on how it shapes emotional coping strategies and influences emotional well-being. As social media has become deeply embedded in adolescents' daily lives, it plays an important role in their social and emotional experiences. Drawing on the Uses and Gratifications Theory, this study explores the motives underlying social media use to fulfill emotional and psychological needs among adolescents experiencing disharmonious family relationships. A qualitative descriptive approach was employed involving 24 Indonesian adolescents who met the study's inclusion criteria. Data were collected through in-depth interviews and observations of participants' everyday social media use. The findings show that social media functions as an emotional coping mechanism, enabling adolescents to regulate emotions and manage personal stress. Scrolling emerged as the most common activity for emotional distraction, while liking, sharing, and commenting served as forms of social validation. Consequently, many participants spent more time engaging with social media than interacting with their families. The emotional connections formed through social media fulfilled needs that remained unmet within their family environments. Among the available platforms, Instagram was the most preferred because its features best accommodated participants' emotional needs and preferences.